3-dimensional inkjet printing of macro structures from silver nanoparticles - Vaithilingam, Jayasheelan; Saleh, Ehab; Körner, Lars; Wildman, Ricky D.; Hague, Richard J.M.; Leach, Richard K.; Tuck, Christopher J. (Elsevier, 2018)
The adoption of additive manufacturing technology is gaining interest for processing precious metals. In this study, the capability of inkjet printing was explored to fabricate macroscopic parts from commercial silver nanoparticle ink (AgNPs). A bespoke JETx® three dimensional (3D) inkjet printing machine was used to print and subsequently sinter up to 1000 layers of AgNPs using an infrared source. Examination of the sample using X-ray computed tomography and scanning electron microscopy revealed the existence of both micro- and nano-scale pores within the structure. Pinning effect, residual surface temperature, insufficient droplet overlap and surface defects were the key factors contributing to the voids. Elemental mapping confirmed the structure to be composed of 87% of silver along with carbon and oxygen. The 750 dpi sample showed a 25% reduction in nanopores and 77% lower micro-pores compared to the 600 dpi sample. In terms of hardness, the 750 dpi sample was 29% harder than the 600 dpi sample, showcasing samples with higher print resolution can contribute towards less voids and improved mechanical properties. Thus by demonstrating the possibility to fabricate dense parts from AgNPs using inkjet technology, this study opens a novel route for processing nano-scale particulates and precious metals in 3D.